THE INTERNATIONAL CENTER OF RESEARCH AND INFORMATION ON THE PUBLIC, SOCIAL AND COOPERATIVE ECONOMY (CIRIEC), A NETWORK TO BETTER UNDERSTAND AND PROMOTE THE SOCIAL ECONOMY AND COOPERATIVE ENTREPRENEURSHIP (Third Sector Social Economic Review, 2017)
CIRIEC is a non-governmental international scientific organization. It is a worldwide network with many members (12 national sections, other institutional members, researchers,…). For many years CIRIEC has realized and published a lot of scientific works on the social economy and especially on cooperatives. This is a long-standing tradition going back to the foundation of CIRIEC in Geneva (Switzerland) in 1947 or even to the foundation of its review The Annals of Public and Cooperative Economics in 1908 Most of these works are now realized by working groups set up with members of our scientific network. These groups usually publish their final results as a “collective” book under the editorship of those professors who take in charge the scientific coordination of a group. Among the many books published within 30 years on cooperatives and other Social economy organizations I may mention:• ZEVI A. and MONZÓN CAMPOS J. L. (eds), Coopératives, marchés, principes coopératifs, Bruxelles, De Boeck, 1995• COTE D. (ed), Les holdings coopératifs. Evolution ou transformation définitive ?, Bruxelles, De Boeck, 2001• CHAVES R. and SCHEDIWY R. (eds), Gobierno, democracia y directivos en las empresas cooperativas, Revista de economía publica, social y cooperativa, N°48, April 2004• BOUCHARD M. J. (ed), The Worth of the Social Economy. An International Perspective, Peter Lang, 2009• CHAVES R. and DEMOUSTIER D. (eds), The Emergence of the Social Economy in Public Policy. An International Analysis, Peter Lang, 2013• BOUCHARD M. J. and ROUSSELIERE D. (eds), The Weight of the Social Economy. An International Perspective, Peter Lang, 2015.Of course, CIRIEC and its national sections also realize many other researches and publications. For example, CIRIEC carried out some important research programs for the European Union institutions (European Commission, European Parliament, European Economic and Social Committee, …) and for international institutions (International Labour Organization, COPAC (Committee for the Promotion and Advancement of Cooperatives) and so on).The purpose of this article is obviously not to synthetize all this work. It is simply to present the main topics currently dealt with by CIRIEC’s scientific network and to develop the current issues on its agenda.The two main themes studied by the members of CIRIEC’s scientific network during the last years are, firstly, the relation between social economy organizations and territories and, secondly, the evaluation of the social economy especially in the European Union.
Keywords: CIRIEC; non-governmental organization; scientific network